Homenaje a Rigas Velestintís (1757-1798) Precursor de la Independencia de Grecia, humanista, héroe y mártir - Castillo Didier, Miguel (Byzantion Nea Hellás, 2015)
In this article the author draws a biographical outline about Rigas Velestinlis (1757-1798), who was percursor and protomarthyr of the Greek independence. After reconstituing his early years (childhood and early youth) – about which there are very few pieces of trustable information –, Professor Castillo Didier follows the precursor’s life in Constantinople and in the Danuvian princedoms. After that, the first Rigas’ publications are presented, to finally focus on his many activities in Vienna between August 1797 and December 1798. Those activities were mainly as writer, publisher and propagandist of revolutionary ideas, as well as creator of a concrete plan of insurrection against the Ottoman tyranny. It is difficult to attach greater importance to sorne aspects of Rigas’ action and writings than others. The THURIOS, HUMAN RIGHTS, THE HELLENIC REPUBLIC CONSTITUTION: all of them are considered as extraordinary works for their time, even for ours. It is remarkable their deep sense of humanism and of brotherhood between the Balkan peoples, a high teaching vocation, a complete and sincere will of freedom. Finally, the works tells about the treason and imprisonment against Rigas and his seven comrades, and how they were given up by the Austrian absolutism to the Ottoman tyranny.